2020
DOI: 10.1021/jacs.0c04422
|View full text |Cite
|
Sign up to set email alerts
|

Homobenzylic Oxygenation Enabled by Dual Organic Photoredox and Cobalt Catalysis

Abstract: Activation of aliphatic C­(sp3)–H bonds in the presence of more activated benzylic C­(sp3)–H bonds is often a nontrivial, if not impossible task. Herein we show that leveraging the reactivity of benzylic C­(sp3)–H bonds to achieve reactivity at the homobenzylic position can be accomplished using dual organic photoredox/cobalt catalysis. Through a two-part catalytic system, alkyl arenes undergo dehydrogenation followed by an anti-Markovnikov Wacker-type oxidation to grant benzyl ketone products. This formal hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…The addition of the so-formed alkyl radical to another equivalent of heteroarene 1-H + followed by hydrogen atom removal would give the desired alkylated heteroarene 3-H + . Meanwhile, to efficiently quench the generated radical intermediate II, a readily accessible cobaloxime catalyst [Co(dmgH) 2 (py)]Cl was introduced to the system [51][52][53][54][55] not only to prevent the over-reduction of intermediate II but also to serve as a terminal oxidant for the rearomatisation of alkylated intermediate III though H 2 evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the so-formed alkyl radical to another equivalent of heteroarene 1-H + followed by hydrogen atom removal would give the desired alkylated heteroarene 3-H + . Meanwhile, to efficiently quench the generated radical intermediate II, a readily accessible cobaloxime catalyst [Co(dmgH) 2 (py)]Cl was introduced to the system [51][52][53][54][55] not only to prevent the over-reduction of intermediate II but also to serve as a terminal oxidant for the rearomatisation of alkylated intermediate III though H 2 evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Note that electrolysis in the absence of TEMPO resulted in sluggish conversion. This method demonstrated excellent compatibility with primary (3-10), secondary (11)(12)(13)(14)(15)(16)(17)(18), and tertiary (19)(20)(21)(22) alkylorganotrifluoroborates, providing easy access to acridinium dyes with different steric properties. A highly useful feature of our method is that the monoalkylated product can be alkylated again following the above experimental procedures to furnish novel, 3,6-dialkylated acridinium dyes, using the same (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) The alkylation reaction could be scaled up to decagram without difficulty by employing a continuous-flow photochemical reactor 45,46 and a electrochemical batch reactor, as demonstrated in the synthesis of 10.88 g of 36 in 80% yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Nicewicz et al reported a homobenzylic oxygenation reaction achieved by dual organic photoredox and cobalt catalysis (Scheme 13a). [81] The selective oxidation at the homobenzylic positions rather than at the more reactive benzylic positions was achieved in the presence of stoichiometric LiNO 3 as the source of hydrogen atom abstractors. A well-tailored Co II catalyst (36) proved to be more active than the previously reported Co III catalysts (30 and 33).…”
Section: Dual Photocatalyzed Hat and Cobalt Catalysismentioning
confidence: 99%